Epistéme - Zoungrana, Jean (Mnemosine, 2015)
Tradução de ZOUNGRANA, E. Épistémè. In: BERT, J.-F. & LAMY, J. Michel Foucault: un héritage critique. Paris: CNRS, 2014, p. 103-112. Tradutor: Alessandro Francisco.